2019
DOI: 10.1186/s43054-019-0003-9
|View full text |Cite|
|
Sign up to set email alerts
|

Early outcomes of tapering jejunoplasty by antimesenteric seromuscular stripping and mucosal inversion for proximal jejunal atresia

Abstract: Background: High jejunal atresia is associated with significant dilatation of the proximal segment. This poses two problems: (a) calibre discrepancy with the distal unused segment and (b) hypomotility causing stasis. Tapering jejunoplasty/enteroplasty could offer a practical solution in selected cases, leading to early establishment of feeds. This work aims to evaluate the outcome of tapering jejunoplasty including its effect on establishing enteral feeding in neonates with proximal jejunal atresia. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In total, 22 studies reported on paralytic ileus and entailed 1,332 patients and 120 events of paralytic ileus [ 35 , 42 , 46 , 48 , 49 , 51 , 61 , 65 , 81 , 82 , 96 , 98 , 100 , 103 , 109 , 112 , 114 , 115 , 132 , 151 , 153 , 155 ]. The pooled proportion of total paralytic ileus was 0.07 (95%-CI: 0.05–0.11; I 2 =71%, p≤0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 22 studies reported on paralytic ileus and entailed 1,332 patients and 120 events of paralytic ileus [ 35 , 42 , 46 , 48 , 49 , 51 , 61 , 65 , 81 , 82 , 96 , 98 , 100 , 103 , 109 , 112 , 114 , 115 , 132 , 151 , 153 , 155 ]. The pooled proportion of total paralytic ileus was 0.07 (95%-CI: 0.05–0.11; I 2 =71%, p≤0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies reporting on anastomotic stenosis within one month of follow-up, 365 patients were included and 22 events of anastomotic stenosis occurred [ 13 , 18 , 20 , 35 , 57 , 59 , 64 , 75 , 78 , 108 , 109 , 118 , 129 , 151 ].…”
Section: Resultsmentioning
confidence: 99%